Differential Pharmacological Effects on Brain Reactivity and Plasticity in Alzheimer’s Disease - Brem, Anna-Katharine; Atkinson, Natasha; Seligson, Erica; Pascual-Leone, Alvaro (Frontiers in Psychiatry, 2013)
Acetylcholinesterase inhibitors (AChEI) are the most commonly prescribed monotherapeutic medications for Alzheimer’s disease (AD). However, their underlying neurophysiological effects remain largely unknown. We investigated the effects of monotherapy (AChEI) and combination therapy (AChEI and memantine) on brain reactivity and plasticity. Patients treated with monotherapy (AChEI) (N=7) were compared to patients receiving combination therapy (COM) (N=9) and a group of age-matched, healthy controls (HC) (N=13). Cortical reactivity and plasticity of the motor cortex (MC) were examined using transcranial magnetic stimulation (TMS). Cognitive functions were assessed with the cognitive subscale of the Alzheimer Disease Assessment Scale (ADAS-Cog), activities of daily living with the ADCS-ADL. In addition we assessed the degree of brain atrophy by measuring brain-scalp distances in seven different brain areas. Patient groups differed in resting motor threshold and brain atrophy, with COM showing a lower motor threshold but less atrophy than AChEI. COM showed similar plasticity effects as the HC group, while plasticity was reduced in AChEI. Long-interval intracortical inhibition (LICI) was impaired in both patient groups when compared to HC. ADAS-Cog scores were positively correlated with LICI measures and with brain atrophy, specifically in the left IPL. AD patients treated with mono- or combination therapy show distinct neurophysiological patterns. Further studies should investigate whether these measures might serve as biomarkers of treatment response and whether they could guide other therapeutic interventions.